Radiation induced defects of zinc oxide particles with star and flower shapes - Dudin Andrey; Iurina Viktoria; Neshchimenko Vitaly; Li Chundong (St. Petersburg Polytechnical University Journal. Physics and Mathematics, 2022)
The paper presents the results of modeling a proton beam with energies of 100 keV on zinc oxide particles, with star and flower shapes, in the Geant4 software package. A high ability to accumulate primary defects was demonstrated for star-type particles in comparison with flower-type particles. A comparative analysis of the calculated data on the study of defects as a result of modeling with experimental data is carried out.